Taxonomic study of the leafhopper genus Thagria Melichar (Hemiptera: Cicadellidae: Coelidiinae) from Guangxi, China - Fan, Zhi-Hua; Li, Zi-Zhong; Dai, Ren-Huai (Zootaxa, 2015)
The paper deals with 21 valid species of the genus Thagria from Guangxi Autonomous Region, China. Eight new species are described and illustrated: T. biprocessa Fan & Dai, sp. nov., T. decussata Fan & Dai, sp. nov., T. irregularis Fan & Dai, sp. nov., T. multispinosa Fan & Dai, sp. nov., T. paramultipars Fan & Li, sp. nov., T. triangula Fan & Li, sp. nov., T. trifasciata Fan & Li, sp. nov. and T. webbi Fan & Li, sp. nov.. A key is given to distinguish all species of this genus from Guangxi, China and maps showing the geographic distribution of new species are also provided. The name Thagria xuae nom. emend. is given for T. xui Nielson.